Hydantoin Derivatives of L- and D-amino acids: Synthesis and Evaluation of Their Antiviral and Antitumoral Activity - Mladen Mintas; Erik De Clercq; Jan Balzarini; KreÅ¡imir Pavelic; Marijeta Kralj; Katja Ester; Silvana Raic-Malic; Branka Zorc; Zrinka Rajic (Molecules, 2006)
3,5-Disubstituted hydantoin (1,3-imidazolidinedione) derivatives 5a-h wereprepared by base induced cyclization of the corresponding N-(1-benzotriazolecarbonyl)-L-and D-amino acid amides 4a-h. Compounds 5a-h were evaluated for their cytostatic andantiviral activities. Among all the compounds evaluated, 3-benzhydryl-5-isopropylhydantoin (5a) showed a weak but selective inhibitory effect against vaccinia virus (EC50 =16 Î¼g/mL; selectivity index: 25). 3-Cyclohexyl-5-phenyl hydantoin (5g) showed inhibitoryactivity against cervical carcinoma (HeLa, IC50 = 5.4 Î¼M) and breast carcinoma (MCF-7,IC50 = 2 Î¼M), but also cytotoxic effects towards human normal fibroblasts (WI 38). On thecontrary, the 3-benzhydryl-5-phenyl substituted hydantoin derivative 5h showed moderateinhibitory activity towards HeLa, MCF-7, pancreatic carcinoma (MiaPaCa-2), lungcarcinoma (H 460) and colon carcinoma (SW 620) (IC50 = 20â23 Î¼M), but no effect on WI38.